At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To solve the problem of factoring the binomial [tex]\(8x^3 + 125y^3\)[/tex], we need to use the sum of cubes formula. The sum of cubes formula is expressed as:
[tex]\[ a^3 + b^3 = (a + b)(a^2 - ab + b^2) \][/tex]
First, we identify the terms [tex]\(a\)[/tex] and [tex]\(b\)[/tex] from the given binomial [tex]\(8x^3 + 125y^3\)[/tex]:
[tex]\[ a^3 = 8x^3 \quad \text{and} \quad b^3 = 125y^3 \][/tex]
Since [tex]\(8x^3 = (2x)^3\)[/tex] and [tex]\(125y^3 = (5y)^3\)[/tex], we can identify:
[tex]\[ a = 2x \quad \text{and} \quad b = 5y \][/tex]
Next, applying the sum of cubes formula [tex]\(a^3 + b^3 = (a + b)(a^2 - ab + b^2)\)[/tex]:
[tex]\[ 8x^3 + 125y^3 = (2x + 5y)((2x)^2 - (2x)(5y) + (5y)^2) \][/tex]
Now we expand and simplify the expression inside the parentheses:
[tex]\[ (2x + 5y)((2x)^2 - (2x)(5y) + (5y)^2) \][/tex]
Calculate each term individually:
[tex]\[ (2x)^2 = 4x^2 \][/tex]
[tex]\[ (2x)(5y) = 10xy \][/tex]
[tex]\[ (5y)^2 = 25y^2 \][/tex]
Putting it all together in the expression:
[tex]\[ (2x + 5y)(4x^2 - 10xy + 25y^2) \][/tex]
From this, we can see that the missing term inside the parentheses is [tex]\(10xy\)[/tex].
Therefore, the missing term in the factorization [tex]\(8x^3 + 125y^3 = (2x + 5y)(4x^2 - ? + 25y^2)\)[/tex] is:
[tex]\[ 10xy \][/tex]
So, the answer is:
[tex]\[ \boxed{10xy} \][/tex]
[tex]\[ a^3 + b^3 = (a + b)(a^2 - ab + b^2) \][/tex]
First, we identify the terms [tex]\(a\)[/tex] and [tex]\(b\)[/tex] from the given binomial [tex]\(8x^3 + 125y^3\)[/tex]:
[tex]\[ a^3 = 8x^3 \quad \text{and} \quad b^3 = 125y^3 \][/tex]
Since [tex]\(8x^3 = (2x)^3\)[/tex] and [tex]\(125y^3 = (5y)^3\)[/tex], we can identify:
[tex]\[ a = 2x \quad \text{and} \quad b = 5y \][/tex]
Next, applying the sum of cubes formula [tex]\(a^3 + b^3 = (a + b)(a^2 - ab + b^2)\)[/tex]:
[tex]\[ 8x^3 + 125y^3 = (2x + 5y)((2x)^2 - (2x)(5y) + (5y)^2) \][/tex]
Now we expand and simplify the expression inside the parentheses:
[tex]\[ (2x + 5y)((2x)^2 - (2x)(5y) + (5y)^2) \][/tex]
Calculate each term individually:
[tex]\[ (2x)^2 = 4x^2 \][/tex]
[tex]\[ (2x)(5y) = 10xy \][/tex]
[tex]\[ (5y)^2 = 25y^2 \][/tex]
Putting it all together in the expression:
[tex]\[ (2x + 5y)(4x^2 - 10xy + 25y^2) \][/tex]
From this, we can see that the missing term inside the parentheses is [tex]\(10xy\)[/tex].
Therefore, the missing term in the factorization [tex]\(8x^3 + 125y^3 = (2x + 5y)(4x^2 - ? + 25y^2)\)[/tex] is:
[tex]\[ 10xy \][/tex]
So, the answer is:
[tex]\[ \boxed{10xy} \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.